Bridging Viral Oncology and Precision Medicine: Leveraging Molecular Signatures of Oncoviruses for Liquid Biopsies and Non-invasive Surveillance - Nzube F. Ekpunobi; Chidimma R. Chukwunwejim; Oghonyon I. Eddison; Sandra C. Okoye; Theresa Ariri; Michael Kyere; Malachy C. Ugwu (Journal of Scientific Research and Reports, 2026)
Oncogenic viruses contribute substantially to the global burden of malignancy and remain an important challenge for cancer prevention, early detection, and surveillance. This review examines the molecular signatures associated with major oncogenic viruses, including human papillomavirus, hepatitis B virus, hepatitis C virus, Epstein–Barr virus, Kaposi’s sarcoma-associated herpesvirus, and Merkel cell polyomavirus. The manuscript discusses key mechanisms through which viral infections promote carcinogenesis, including viral genome integration, disruption of tumour suppressor pathways, chronic inflammation, immune modulation, and immune evasion. Particular attention is given to molecular alterations that may serve as clinically useful biomarkers, such as viral oncoprotein activity, circulating tumour DNA, altered DNA methylation patterns, and dysregulated non-coding RNAs. The review also considers the translational relevance of these molecular signatures for liquid biopsy approaches, multi-cancer early detection platforms, and biomarker-driven surveillance in high-risk populations. These strategies may support earlier recognition of virus-associated malignancies and improve monitoring where conventional tissue-based diagnostics are difficult to apply. However, clinical implementation remains limited by assay variability, insufficient longitudinal validation, unequal access to molecular diagnostics, and the need for standardised workflows across different healthcare settings. The burden of virus-associated cancers is especially important in low- and middle-income settings, where vaccination, screening, and diagnostic infrastructure may be limited. Overall, the review highlights the potential value of integrating viral oncology with precision medicine while emphasising the need for cautious interpretation, rigorous validation, and equitable implementation of biomarker-based screening and surveillance strategies.